2018
DOI: 10.1101/374272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Static stability predicts the continuum of interleg coordination patterns inDrosophila

Abstract: statement: 20A simple stability-based modelling approach can explain why walking insects use different 21 leg coordination patterns in a speed-dependent way. 22 23 Abstract 24During walking, insects must coordinate the movements of their six legs for efficient 25 locomotion. This interleg coordination is speed-dependent; fast walking in insects is 26 associated with tripod coordination patterns, while slow walking is associated with more 27 variable, tetrapod-like patterns. To date, however, there has been no … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…To optogenetically manipulate motor neuron activity during walking, we positioned tethered flies on a spherical treadmill ( i.e ., a Styrofoam ball) within a visual arena ( Reiser and Dickinson, 2008 ; Figure 7D ). Previous studies have found that walking speed and gait on the treadmill are similar to freely walking flies ( Szczecinski et al, 2018 ). In our setup, the fly was motivated to walk forward with a wiggling stripe ( Figure 7E ), and we tracked the treadmill and the fly’s behavior with multiple high-speed cameras.…”
Section: Resultsmentioning
confidence: 86%
“…To optogenetically manipulate motor neuron activity during walking, we positioned tethered flies on a spherical treadmill ( i.e ., a Styrofoam ball) within a visual arena ( Reiser and Dickinson, 2008 ; Figure 7D ). Previous studies have found that walking speed and gait on the treadmill are similar to freely walking flies ( Szczecinski et al, 2018 ). In our setup, the fly was motivated to walk forward with a wiggling stripe ( Figure 7E ), and we tracked the treadmill and the fly’s behavior with multiple high-speed cameras.…”
Section: Resultsmentioning
confidence: 86%
“…In a recent modelling study, Szczecinski et al [46] demonstrated that interleg coordination patterns in D. melanogaster result from the interplay between static stability of the animal and robustness of the coordination pattern. The authors found that at a large variety of walking speeds (hence coordination patterns), only the ipsilateral phase differences change, whereas contralateral phase differences remain at about 1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in FLx over a step can displace the fly's center of stability away from its center of mass (Figure 5G), thereby momentarily decreasing posture stability. 65,66 To recover stability, posture control systems could either adjust lateral foot placement in the next step, like in humans, 67 or dynamically engage viscoelastic properties of the musculoskeletal system, as observed in the cockroach. 68 Our data are consistent with the first possibility.…”
Section: Visual Feedback Prevents Pairwise Interlimb Correlations Underlying Postural Adjustmentsmentioning
confidence: 99%